Perception of altered smile esthetics among Moroccan professionals and lay people - L. Ousehal; H. Aghoutan; S. Chemlali; I. Filali Anssari; N. Talic (Saudi Dental Journal)
Objective: To evaluate and compare the impact of altered smile characteristics on the perception of smile esthetics between Moroccan dentists and lay people. Materials and methods: Thirty-four digital smile photographs displaying alterations in crown length and width, lateral incisor gingival margin position, gingival exposition, midline diastema, and upper midline deviation were presented to a sample of 30 dentists and 30 lay people. The ratings were assessed with a visual analog scale. Results: Compared to that of lay people, Moroccan dentists’ evaluation of the gingival smile was more critical when the decrease in central incisor crown length was 2.5 mm (p < 0.001) or greater and when the increase in gingival exposition was 4 mm or greater (p < 0.01). Moroccan dentists were also critical in their evaluation of maxillary lateral incisor crown width alterations (p < 0.05) and incisal midline deviations (p < 0.05). However, the professionals and lay people similarly evaluated irregularities in the incisor gingival margin position. Increases in the midline diastema were judged critically by both Moroccan dentists and lay people. Conclusions: In this sample, Moroccan dentists evaluate smile esthetic alterations more critically than Moroccan lay people. This difference in perception of smile discrepancies must be taken into account during the finishing phases of orthodontic treatment and restoration of the anterior teeth in Moroccan patients. Keywords: Patient perception, Dentist perception, Smile esthetics, Orthodontists, Lay people, Visual analog scale